The Effect of the Teaching at the Right Level (TaRL) Approach on Students’ Critical Thinking Skills in Learning Fractions in Grade IV of Elementary School in Bogor, Indonesia - Lilis Supratman; Wandi Saputra; Reni Winarsih (MASI Mandiri Edukasi, 2025)
This research examines the effect of the Teaching at the Right Level (TaRL) approach on the critical thinking skills of Grade IV elementary students while they are studying fractions. The study aims to enhance students' critical thinking abilities by implementing TaRL. Employing a quasi-experimental method with a pretest-posttest control group design, the study involved 41 SDN Polisi 2 Bogor fourth-grade students. Two classes, IVA and IVB, were selected through saturation sampling. Data collection tools included a 10-item critical thinking test and an observation sheet to assess critical thinking skills. Results indicate a significant enhancement in students' critical thinking skills with the TaRL approach, supported by hypothesis testing that yields a significance value of 0.000 (p < 0.05), leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (H1). N-Gain test outcomes further illustrate the effectiveness of TaRL in improving critical thinking abilities, particularly in IVB class mathematics lessons on fractions, while fostering increased engagement and deeper conceptual understanding among students. These findings suggest that the TaRL approach can be incorporated into mathematics learning to enhance students’ critical thinking and conceptual grasp.